2014
DOI: 10.17795/jjnpp-17368
|View full text |Cite
|
Sign up to set email alerts
|

Use of Herbal Medicine Among Pregnant Women on Antenatal Care at Nekemte Hospital, Western Ethiopia

Abstract: Background: Investigations across the world confirm dramatic increment in the use of complementary and alternative medicine in pregnant women. The most important aspect is lack of awareness of pregnant women about potential effects of using traditional medicine on fetus; some herbal products may be teratogenic in human and animal models. In this area, so far, no research has been conducted in Ethiopia to assess traditional medicine use in pregnant women. Objectives: Therefore, the main objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
66
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 5 publications
(10 reference statements)
27
66
6
1
Order By: Relevance
“…Previous study findings indicated that women with low income may experience limited autonomy as compared to their male counterparts (on whom they may be dependent) who may be responsible for making decisions concerning women's health care choices and wellbeing [47,48]. Our analysis also shows that older age (≥ 35 years) and having children were associated with an increased use of traditional medicine for maternal wellbeing and is consistent with previous studies [41,[49][50][51]. This could be possibly due to the fact that these women may have spent more time in Africa and thus had pre-migration experiences of using traditional medicine.…”
Section: Discussionsupporting
confidence: 91%
“…Previous study findings indicated that women with low income may experience limited autonomy as compared to their male counterparts (on whom they may be dependent) who may be responsible for making decisions concerning women's health care choices and wellbeing [47,48]. Our analysis also shows that older age (≥ 35 years) and having children were associated with an increased use of traditional medicine for maternal wellbeing and is consistent with previous studies [41,[49][50][51]. This could be possibly due to the fact that these women may have spent more time in Africa and thus had pre-migration experiences of using traditional medicine.…”
Section: Discussionsupporting
confidence: 91%
“…84 TCAM users were also found to be younger (<30 years) 84 98 and married 84 98 compared with non-TCAM users. 24 Meanwhile, three studies from Zambia, 82 Mali 90 and Ethiopia 83 reported no sociodemographic difference between TCAM users and non-users. With regard to TCAM use during childbirth, two studies drawn from a large sample of Nigerian women show TCAM users are likely to be women who are less educated, from low socioeconomic background, Muslim and primiparous.…”
Section: Prevalence Of Concurrent Use Of Tcam and Allopathic Medicinesmentioning
confidence: 99%
“…The level of use of herbal medicine is similarly high in a number of other studies in sub-Saharan Africa, Asia and Middle East, where the proportions of use have been observed to range between 20-80% [5,6,[14][15][16]. Findings in all these studies ratify dramatic increment in the use of herbal medicines in pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 55%
“…For many years, women used herbal medicines in pregnancy to sort out several conditions during pregnancy and the delivery process. Similar to ndings in Tabora, studies indicate that pregnant women in some communities use herbs for the purpose of easing pain, accelerating labour, preventing antepartum and postpartum haemorrahage, increasing milk production, and aiding postpartum uterine involution [7,15,26]. The grounds for the high usage of herbs could in addition be attributed to their easy accessibility, perceptions that they are safe; as well as the general lack of awareness of the potential side effects [18,24,27].…”
Section: Discussionmentioning
confidence: 71%